2018
DOI: 10.1007/s10346-018-0949-5
|View full text |Cite
|
Sign up to set email alerts
|

Coastal lateral spreading in the world heritage site of the Tramuntana Range (Majorca, Spain). The use of PSInSAR monitoring to identify vulnerability

Abstract: Coastal lateral spreading in the world heritage site of the Tramuntana Range (Majorca, Spain). The use of PSInSAR monitoring to identify vulnerability Abstract The Bàlitx area is located on the steep coastal side of the Tramuntana Range (Majorca), a mountainous region which was declared a World Heritage Site by UNESCO in 2011 in the cultural landscape category. The Bàlitx site was occupied by farming areas with dry stone constructions and water storing systems of both Roman and Islamic origin. The coastal land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Delgado et al [63] measured by InSAR rates resembling that of Chgega (2-4 mm/yr) in a compound rotational DGSD of large dimensions in the Sierra de Aitana (Spain). Mateos et al [17] reported an average velocity of the same order of magnitude (5.2 mm/yr) in a large lateral spreading along the North coast of Majorca (Spain). Extensive lateral spreading and block sliding processes in a geological setting comparable to the Chgega landslide have been under investigation since 2006 in the North part of Malta [8,9,[64][65][66].…”
Section: Motion Detected In Chgega and In Other Similar Landslidementioning
confidence: 91%
See 1 more Smart Citation
“…Delgado et al [63] measured by InSAR rates resembling that of Chgega (2-4 mm/yr) in a compound rotational DGSD of large dimensions in the Sierra de Aitana (Spain). Mateos et al [17] reported an average velocity of the same order of magnitude (5.2 mm/yr) in a large lateral spreading along the North coast of Majorca (Spain). Extensive lateral spreading and block sliding processes in a geological setting comparable to the Chgega landslide have been under investigation since 2006 in the North part of Malta [8,9,[64][65][66].…”
Section: Motion Detected In Chgega and In Other Similar Landslidementioning
confidence: 91%
“…Our description of Chgega Mountain has benefited from new data gathered through up-to-date remote sensing (RS) techniques: landscape analysis, Uncrewed Aerial Vehicle Digital Photogrammetry (UAV-DP), and advanced Satellite InSAR techniques. The combination of the two latter techniques has already proven its usefulness for landslide characterization elsewhere (see for example the studies of Cigna et al [16] in Ireland, Mateos et al [17] in Spain, or Hopffer Martins et al [18] in Timor-Leste). The focus here, in turn, is on a region where RS methods are not yet common.…”
Section: Introductionmentioning
confidence: 99%
“…The landscape is marked by agricultural terraces constructed in dry stone to extend farmland. The terraces have also played an important role in preventing damage from soil erosion and very frequent slope movements [125]. Pine and holm oaks forest and a rich shrub layer mainly cover the range.…”
Section: Balearic Islandsmentioning
confidence: 99%
“…In particular, landslides are common along the European coasts of the Mediterranean Sea and can include different types of transport mechanisms such as falls, slides, spreads, or flows [9][10][11][12][13][14]. Among these, lateral spreading and block sliding processes are widely represented in the Mediterranean coasts, such as in northern Mallorca (Spain) [15], in the western part of Liguria (Northern Italy) [16], Tropea area (Southern Italy) [17], Scopello in northern Sicily [18] and in the Maltese islands [14,19,20].…”
Section: Introductionmentioning
confidence: 99%